The influence of anthropometric parameters on the concentration of globulin that binds sex hormones during the menopausal transition - Dženana Softić; Lejla Mešalić; Delila Softić (Medicinski glasnik, 2024)
Aim: To determine the effect of body mass index (BMI) and waist-hip ratio (WHR) on the concentration of circulating sex hormone-binding globulin (SHBG) throughout the menopausal transition. Methods: This cross-sectional study included 150 women divided into three groups: premenopausal (n=50), perimenopausal (n=50), and postmenopausal (n=50). The processing of the test women consisted of three phases: inter-view, blood sampling and determination of BMI and WHR. The SHBG concentration was determined from the blood, and BMI and WHR were measured. Results: The BMI and WHR of the post-menopausal women were significantly higher comparing to the other two groups, while the postmenopausal SHBG was significantly lower compared to the premenopausal con-centration. In all three groups, a significant negative correlation was found between SHBG and BMI (Rho= -0.385; p<0.05), and between SHBG and WHR (Rho= -0.411; p<0.05). By the univariate regression analysis model, it was determined that BMI (?= -0.594; p<0.001) and WHR (?= -0.407; p=0.003) were independently negative predictors of SHBG in postmenopausal women, while in the multivariate regression analysis model only BMI as an independently negative predictor of SHBG in postmenopausal women was found (?= -0.263; p=0.024). Conclusion: The value of SHBG during the menopausal transition decreases and women with higher BMI and WHR have lower values of SHBG regardless of the duration of menopause. Considering the connection between SHBG and anthropometric parameters, and the drop in its values upon entering and passing through the menopausal transition as such it can be used as a predictor for an increased risk of cardiovascular diseases and metabolic syndrome in a selected group of women.
Keywords: body mass index; menopause; obesity; SHBG; waist-hip ratio